A.J.P. Taylor and his The Origins of the Second World War - Perman, Tomáš (Dějiny – teorie – kritika, 2024)
The article looks at the now already legendary work by the prominent British historian A.J.P. Taylor The Origins of the Second World War. At the tie of its publication (1961) the book challenged the conventional academic view of Hitler that saw him simply as an embodiment of evil, responsible for the Second World War. By contrast Taylor presented Hitler as an opportunist who exploited disputes between the great European powers and strove for dominance in Europe but did not wish to unleash a world war, instead hoping just to provoke a series of short localised conflicts to achieve his objective. The second part of the article is devoted to the extensive discussion that followed the publication of Taylor´s controversial book.